The Impact Of Green Finance On The National Debt: Model Analysis Of Cdp And Evaluation Of The Intensity Of Mission - Sandro Turina; Giuseppe Confessore; Maurizio Turina (European Regional Science Association (ERSA), 2013)
The Energy Service Company (ESCO also called) are companies which carry out actions to improve energy efficiency, taking upon himself the risk of the initiative and freeing the end user from any organizational effort and investment. The economic savings obtained are shared between the ESCO and the final customer with different types of trade agreement. Usually the intervention methodology is divided into the stages of 'Energy Diagnosis' designed to identify waste, inefficiency and misuse that produces the elements to prepare a rough draft of the measures to be implemented and the management and maintenance of the plants to all over the agreed period. The idea of supporting the implementation of energy saving policies in protecting the environment, in line with the procedure provided for by Agenda 21 and in full respect of virtuous actions to reduce costs in the delivery of public services, is framed in the management separate Deposits and Loans in Italy finances about 40% of the national debt. This type of action, capable of ensuring budgetary savings through the introduction of technology (eg LED, photovoltaic, thermal, wind, etc ...) to cover obligations necessary for the realization of the investment, expresses a significant market whose size could already in first instance be estimated from the analysis of the consolidated entity, the analysis of georeferenced maps (GIS) and satellite data (SAR) today normally available to the local authority and national agencies in order to estimate with sufficient accuracy the potential of renewable energy actually achievable in 'public areas' from sources such as wind, offshore wind, hydro, mini-water, photovoltaic, thermal. .......... The research team, after estimating the demand for debt financing that the CDP model is now able to meet, analyze the impact of this model may have on the budgets of local authorities both in terms of improvement in the credit standing of 'local authority, both in terms of reducing the cost of management of major public infrastructure through the construction of an indicator of the intensity of the mission which the financial instruments could be compared to the classic green finance support to local authorities expressed today by the system the nation's credit.
Keywords: 330; Green finance; environmental sustainability; energy policies; practices